Discrimination in the Equilibrium Search Model with Wage-Tenure Contracts - Fang, Zheng (2016)
This paper extends Burdett and Coles (2003)’s search model to two types of workers and firms and derives the equilibrium earnings distributions for both types of workers. It is proven that minority workers have a higher unemployment rate than majority workers; discriminating firms make lower profit than non-discriminating firms; offers to minority workers by non-discriminating firms are consistently superior to those by discriminating firms, and at the same wage level, majority workers almost always experience a faster wage increase than the minority workers.